Key areas for improving the professional selection of judges in Ukraine - Chudyk, Nataliіa (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article analyses and suggests the main directions of improvement of professional selection of judges in Ukraine.It is proved that the main directions of improvement of the procedure of appointment and selection of judges in Ukraine can be applied comprehensively or refer to individual elements of its mechanism. As a result of the scientific analysis of the international experience in improving the procedure of appointing judges and the general approach to the reform of the judicial system in Ukraine, the following recommendations are made: to establish the independence of the judiciary from any political influence; to ensure transparency and maximum publicity of the judicial selection process; to establish a clear, specific, professional standard for judges, which should specify and define the necessary skills, knowledge and moral qualities, experience, which are mandatory for candidates for the position of judge; taking into account best international practices, provide professional training for candidates for the judiciary, including internships and training programmes; ensure compliance with the principle of non-discrimination among judges, as well as in the High Judicial Council and the High Qualification Commission of Judges of Ukraine; take clear and concrete anti-corruption measures leading to the introduction of mechanisms for vetting candidates for the absence of corrupt links; provide legal guarantees for the establishment of objective and independent judicial bodies; monitoring and evaluation of the quality of judges' work on an ongoing basis to ensure that the judicial system functions at a high level; involvement of international organisations and experts in the process of selecting judges, which will help to introduce international standards and best practices into the judicial system of Ukraine.